2007
DOI: 10.1007/s00024-007-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of History-Dependent Rheology in Plate Boundary Lubrication for Generating One-Sided Subduction

Abstract: We have developed a two-dimensional dynamical model of asymmetric subduction integrated into the mantle convection without imposed plate velocities. In this model we consider that weak oceanic crust behaves as a lubricator on the thrust fault at the plate boundary. We introduce a rheological layer that depends on the history of the past fracture to simulate the effect of the oceanic crust. The thickness of this layer is set to be as thin as the Earth's oceanic crust. To treat 1-kilometer scale structure at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 60 publications
(77 reference statements)
1
25
0
Order By: Relevance
“…We also prescribe weak oceanic crust that decouples to a certain degree the sinking slab from the overriding plate causing subduction asymmetry (Crameri et al, 2012;Gerya et al, 2008;Tagawa et al, 2007). The crust is neutrally buoyant, and it follows the same viscosity law as ambient mantle while being 10 times less viscous and more easily deformable.…”
Section: Model Setupmentioning
confidence: 99%
“…We also prescribe weak oceanic crust that decouples to a certain degree the sinking slab from the overriding plate causing subduction asymmetry (Crameri et al, 2012;Gerya et al, 2008;Tagawa et al, 2007). The crust is neutrally buoyant, and it follows the same viscosity law as ambient mantle while being 10 times less viscous and more easily deformable.…”
Section: Model Setupmentioning
confidence: 99%
“…Previous studies showed that weak hydrated crust (sediments, hydrothermally altered basalts, serpentinites) present on top of the terrestrial oceanic plates have an important effect on the style of subduction by acting as a lubricating layer between two converging plates [Lenardic and Kaula, 1994;Gerya et al, 2008;Tagawa et al, 2007]. A common explanation of the weakness of deep faults (up to 200 km depth) is the presence of fluids (CO 2 , H 2 O) released by dehydration or decarbonatization reactions [Peacock, 1990;Schmidt and Poli, 1998].…”
Section: Weak Hydrated Crustmentioning
confidence: 99%
“…Moreover, numerical models of dynamic subduction simulating realistic viscoplastic rheology (including sometimes elasticity) reveal that a low strength interplate plane (γ c < 0.1) is required to model realistic convergence of strong lithospheres (Hassani et al, 1997;Hall and Gurnis, 2003;Sobolev and Babeyko, 2005;Tagawa et al, 2007;Gorczyk et al, 2007). Gerya et al (2008) show that a very high strength contrast between converging plates and the sheared interplate material, favoured by an interplate friction coefficient close to zero, is necessary to model one-sided subduction over a wide range of subducting lithosphere age.…”
Section: Friction Coefficient Along the Interplate Shear Zonementioning
confidence: 99%